Üç Fazlı Dengeli Elektrik Dağıtım Şebekelerinde Kayıp Tahmini Ve Kayıp Paylaşımı - Bozgeyik, Fevzi (Fen Bilimleri Enstitüsü, 2015)
Bu tez çalışması, üç fazlı dengeli elektrik dağıtım şebekelerinde meydana gelecek teknik kayıpları tahmin yöntemi ile bulmayı ve kayıpları tüketicilere adil şekilde paylaştırmayı amaçlamaktadır. Elektrik enerji sistemlerinde en büyük kayıp oranı dağıtım safhasında gerçekleştiği için bu çalışmada dağıtım sistemi üzerinde durulmuştur. Dünya genelinde kişi başına düşen elektrik enerjisi tüketimi artarken, kaynakların kısıtlı oluşu kayıpların azaltılmasını kaçınılmaz kılmaktadır, bunun için öncelikle kayıpların tespiti gereklidir. Diğer taraftan kayıplar, enerji fiyatlandırmasında etken rol oynamakta ve elektrik dağıtım kuruluşlarının rekabet güçlerini sınırlamaktadır. Bu iki temel neden enerji kayıplarının hesaplanmasını ve tüketicileri de ilgilendirdiği üzere adil olarak paylaştırılmasını gerektirmektedir. Kayıplar iki ana sınıfa ayrılır; Teknik kayıplar ve teknik olmayan kayıplar. Yüklerin değişken oluşu anlık kayıpların hesabını zorlaştırırken, sistem bileşenlerinin doğası gereği kaçınılmaz olarak meydana çıkan teknik kayıplar tahmin yöntemleri ile hesaplanabilmektedir. Teknik olmayan kaçak kullanım, hatalı ölçümler ve idari kayıpları ise hesaplamak mümkün değildir. Ancak teknik kayıpları hesaplanmış bir sistemin geriye kalan kayıpları teknik olmayan kayıp olarak sınıflandırılabilir. Teknik kayıplar ise akıma bağımlı ve akımdan bağımsız olarak gruplandırılır. Akımdan bağımsız kayıpların hesabı kolay ve hızlıdır, değişken yük akımına bağımlı kayıpların hesabı için tahmin yöntemleri geliştirilmiştir. Bu çalışmada bileşenlerin değişken kayıplarını en kısa sürede ve kolayca kabul edilebilir seviyede doğruluk oranı ile tahmin edebilen Yük Kayıp Faktörü yöntemi kullanılmıştır. Aynı şebeke Newton-Raphson yük akışı yöntemini kullanan DIgSILENT programı ile çözdürülmüş ve sonuçları kıyaslanmıştır. Yöntemin sonuçları beklenen şekilde iyi çıkmıştır, ancak bazı bileşenlerin kayıplarında büyük fark görülmüştür, üzerinde çalışma gerektirmektedir. Tüketilen güç ile kayıplar arasında lineer olmayan ilişki nedeniyle kayıpların kaynaklarına paylaşımı zordur. Geliştirilmiş kayıp paylaşımı yöntemlerinin hiç biri tam adil sonuç verememektedir. Bu nedenle sistemin kullanıcılarına ve koşullarına bağlı seçilirler. Radyal elektrik dağıtım sistemlerinin topolojisine uygun ve kolay uygulanması nedeniyle bu çalışmada grafik teorisi içeren oransal kayıp paylaşımı yöntemi kullanılmıştır. Yüklerin talep güçlerinin kareleri oranındaki paylaşımda sapmalar olduğu, büyük güçlü yüklere daha fazla kayıp atandığı gözlemlenmiştir. Dağıtım şebekelerinin açık ring şeklinde farklı kombinasyonlarda işletilebilmesi ve dağıtılmış üretime sahip olabilmeleri nedeniyle yapıları değişebilmektedir. Değişen yapıları kayıpların analizinin ve paylaşımının sürekliliğini gerektirmektedir. Bu çalışmada kullanılan YKF ve grafik teorisi ile oransal paylaşım yöntemleri dağıtım şebekesinin farklı çalışma tiplerine uygulanmıştır. En az veri ile en kısa sürede ve kolayca kabul edilebilir hata seviyelerinde sonuçlar vermeleri nedeniyle kurulum öncesi ve işletme sırasında kullanılabilir yöntem oldukları gösterilmiştir. Ancak grafik teorisi ile oransal kayıp paylaşım yönteminin sonuçlarının başka bir yöntem ile kıyaslanması ileriki çalışmaların konusu olabilir.

The purpose of this study is estimation of technical losses of balanced three-phase electricity distribution network with estimation method and allocation of losses to consumers in a fair manner. This study focused on the distribution system because of the biggest loss rate occurs in the distribution phase in energy systems. While increasing of electricity comsumption per capita in the World, limited resources forces to reducing the losses so firstly it is necessary to detect losses. On the other hand, losses plays active role in energy pricing and restrict the competitiveness of electricity distribution companies. These two main reasons requires to calculation of energy losses and allocation the calculated losses to consumers in a fair manner as well. Losses are divided into two main classes; Technical losses and non-technical losses. Technical losses occur due to the nature of the system and equipments. Technical losses can be minimized in the design phase or can be limited at the operation phase with suitable treatments. Current flow dependent and current flow independent losses are composed the technical losses. Current flow independent losses also called as no-load losses. Because these losses can occure at system under voltage, not need to current flow. No-load losses are iron losses of power and voltage-current measurement transformers, dielectric, corona and leakage current losses of cables and capacitors. Current flow dependent losses are caused by the load current and also called as load losses. Varies in proportion to the square of the load current intensity and they occur as heat from power and current measurement transformers and junction points. They constitute a major part of the losses occurring in the power distribution system. Consist of the variable nature of the load current makes it dependent variable and current losses are also variable. Non-technical losses occur from illegal use, faulty measurements and administrative losses. Non-technical losses can be destruct theoretical through study of the electricity distribution companies. However, in practice this is not possible due to varius obstacles and challenges. Separating with a sharp line is not possible technical losses and non-technical losses from each other. Technical and non-technical losses rates varies depending on the cause of each country's development level, length of the transmission and distribution network lines, etc. It is difficult to account the losses instantaneous because of the variable nature of the loads and take measurements from all points to collect data in the distribution system is costly, so often losses are estimated. Load Loss Factor [22], Measurement History [20], Power Flow [25] methods have been developed to estimate the losses. It is not possible to calculate illegal use, faulty measurements and administrative non-technical losses. However, the remaining losses of calculated technical losses of a system can be classified as non-technical losses. In this study Load Loss Factor method is used, which can estimate as soon as the components losses of distribution network easily with acceptable accuracy. Same distribution network was dissolved with DIgSILENT software and results were compared. The results of the method were significantly better as expected. But large differences were found in loss of some components than others, require working on. The technical losses, occur in the power system, have always been a major problem to the pricing of energy. Non-linear relationship between the transmitted or consumed power with losses is difficult to identify the source of the losses [27]. Pro-Rata [29], Inremental allocation [30], Proportional allocation with graph theory [31] and Z-Bus [33] loss allocation methods have been introduced in the literature. None of developed loss allocation method does not give full fair results. Therefore the methods are chosen depending on conditions and system users. Proportional allocation method with graph theory was used in this study due to implementation accordingly to the topology of the radial electric distribution system. In squared proportional allocation method, deviation was observed and further losses are assigned to bigger loads than others. The topologies of open ring and distributed generated distribution systems can be changed, because of operation options in different combinations. Changing topologies require the continuity of the analysis and allocation of losses. At this study, Load Loss Factor and Proportional Allocation with Graph Theory methods were applied to different types of work distribution network. Giving results in acceptable error level easily with minimal data is shown that these methods can be used during operation and design stage. However, the results of proportional allocation with graph theory method can be compare with another method in future studies.
Loss Estimation And Loss Allocation Of Balanced Three-phase Electricity Distrubition Networs
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Dağıtım Şebekeleri; Kayıp Tahmini; Kayıp Paylaşımı; Elektrik Dağıtım Şebekelerinde Teknik Kayıplar; Elektrik Dağıtım Şebekelerinde Teknik Olmayan Kayıplar; Yük Kayıp Faktörü; Grafik Teorisi İle Oransal Kayıp Paylaşımı; Distribution Networks; Loss Estimation; Loss Allocation; Technical Losses At Electrical Distribution Networks; Non-technical Losses At Electrical Distribution Networks; Load Loss Factor; Proportional Loss Allocation With Graph Theory